SCREENING AND IDENTIFICATION OF POTENTIAL BIOACTIVE CONSTITUENTS IN A NEW HERBAL PRESCRIPTION SEAWEED COMPLEX PREPARATION - Liu, Xin; Wen, Songsong; Sun, Zhenliang; Wang, Changyun (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Seaweed Complex Preparation (SCP) is a clinical traditional Chinese medicine preparation composed of seventraditional Chinese herbs, and has been used for treatment of lung cancer, liver cancer and digestive cancer.Materials and Methods: In this study, the potential bioactive constituents of SCP were isolated and identified by chromatographicand spectroscopic methods. The immunomodulatory and DPPH radical scavenging activities of the constituents were also evaluatedin vitro.Results: Forty-three compounds were isolated from the EtOAc and n-BuOH fractions of the decocted extracts. More than 10structural types of chemical constituents were found, including flavonoid glycosides, flavonoids, phenolic acid compounds, lignans,iridoid glycosides, and polysaccharides mainly composed of galactose and glucose. Flavonoid glycosides exhibited potentialimmunomodulatory by promoting splenic lymphocyte proliferation and stimulating the secretion of cytokines IL-2 and IFN-γ, aswell as free radical (DPPH) scavenging activities. Caffeic acid derivatives showed remarkable free radical (DPPH) scavengingactivity, while polysaccharides also displayed immunological enhancement effects.Conclusion: Four molecular communities, flavonoid glycosides, flavonoids, phenolic compounds and polysaccharides, might be thepotential bioactive components of SCP. Synergism of these four molecular communities in SCP may endue the anticancer propertiesand reflect the feature of multi-components and multi-targets of traditional Chinese medicine formula.